STEAM-ME: A Novel Model for Successful Kaizen Implementation and Sustainable Performance of SMEs in Vietnam - Thanh-Lam Nguyen (Complexity)
The current trend of international integration urges every business organizations to continuously improve their competitive advantage for their survival and sustainable growth. And Kaizen has been a preferable approach in practice. Due to the special role of SMEs in the Vietnam economy, improving their competitiveness is critical. Thus, this study is aimed at identifying determinants of the successful Kaizen implementation and sustainable performance so that SMEs can have proper actions and prioritize their operations within their available resources. Through a formal survey of 213 participants from 62 SMEs which have been successful in implementing Kaizen and appropriate statistical analyses, seven important determinants have been identified, namely, (1) supports from senior management; (2) training; (3) environment; (4) assessment; (5) motivation; (6) mindset; and (7) engagement of all members in the organization. Among them, “mindset” is newly proposed in this study through a qualitative research and found as crucial component in the model. The finding obviously fulfills the existing literature. Moreover, the first letters of the identified factors are orderly congregated as “STEAM-ME” which is a novel model for the successful Kaizen implementation and the sustainable performance of SMEs in Vietnam. “STEAM-ME” implies that organizations need to have a new airflow as “steam” to make all of its members refreshed and brimful of energy to gain significant success in implementing Kaizen, and improve their business performance as well as competitive advantage for their sustainable development. Notably, the novel model can efficiently demonstrate organic relationships among its components which all have positive and significant impacts on the successful Kaizen implementation and sustainable performance of SMEs in Vietnam.